SHELF LIFE OF GRAPE FRUIT PEEL PRESERVED CATFISH (Clarias gariepinus) - OLADOSU-AJAYI, R.N; OLATEJU, O.P.; AJAYI, C.T. (Nigerian Journal of Fisheries, 2011)
Hot water extract of grape fruit peel (Citrus paradisa) was used as a preservative for catfish (Clarias gariepinus) to determine if it can extend its shelf life and how the dipping duration affects this. It was observed that hot water extract of grape fruit peel was able to extend the shelf life of catfish (Clarias gariepinus) from the 20 hours to between 24 and 26 hours post – slaughter after which it became unfit for consumption. Also, the dipping duration did not affect the preservative action of hot water extract of grape fruit peel on the fish. Thus, it means that grape fruit peel extract only required a contact with fish for some time to exert its preservative action on it. Keywords: , f,